Fatores motivadores e implicações estratégicas da terceirização em micro e pequenas empresas da Serra Gaúcha - Marquesini, Vanessa Heckler (Universidade do Vale do Rio dos Sinos, 2017)
The objective os this paper was to analyze the main factors that motivate the outsourcing in micro and small companies. The research sugests five hypotheses based on literature and tested them from data survey with micro and small companies located in Serra Gaúcha. The sample consists of 86 companies that include the industry segment, commerce and services. The survey data were analyzed using Structural Equation Modeling. The results show that micro and small companies earn on delivery (reffering to deadlines, both reducing the time between requesting and delivery goods and services to the customers – speed – or delivering on the agreed term – timing) when outsourcing their activities. For the other hypotheses (price, quality, flexibility and service) no significant relationship was found. This paper contributes to enrich both academic field that has a lack on specific studies like this one, as well as the business and environmental fields due the representativeness and relevance of micro and small companies.
Keywords: Terceirização; Micro e pequenas empresas; Estratégia; Modelagem de equações estruturais; Outsourcing; Micro and small companies; Strategy; Structural equation modeling; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis